Dynamic change of fungal community in the gastrointestinal tract of growing lambs - Xue-jiao YIN; Shou-kun JI; Chun-hui DUAN; Pei-zhi TIAN; Si-si JU; Hui YAN; Ying-jie ZHANG; Yue-qin LIU (Journal of Integrative Agriculture, 2022)
Although fungal communities in the gastrointestinal tract have a significant role in animal health and performance, their dynamics within the tract are not well known. Thus, this study investigated fungal community dynamics in the rumen and rectum of lambs from birth to 4 mon of age by using IT1S rDNA sequencing technology together with the RandomForest approach to determine age-related changes in the fungal ecology. The results indicated that gastrointestinal fungal community composition, diversity, and abundance altered (P<0.05) with the increasing age of the lambs. Two phyla, Ascomycota and Basidiomycota, dominated the samples. Similarity within age groups of the rumen fungi increased sharply after 45 days of age, while the similarity increased (P<0.05) significantly after 60 days of age in the rectum. The age-related genera, Acremonium, Microascus, Valsonectria, Myrmecridium, Scopulariopsis, Myrothecium, Saccharomyces, and Stephanonectria, were presented in both ruminal and rectal communities, and their changes in relative abundance were consistent at both sites. The principal coordinates analysis showed significant differences (P<0.05) between the fungal communities in the rumen and rectum. Our findings demonstrate that both the age of lambs and the gastrointestinal tract region can affect the composition of these fungal communities, and this provides new insight and directions for future studies in this research area.